Ultrasound Nomograms of the Fetal Optic Nerve Sheath Diameter - Haratz, Karina Krajden; Melcer, Yaakov; Leibovitz, Zvi; Feit, Hagit; Lerman-Sagie, Tally; Lev, Dorit; Ginath, Shimon; Gindes, Liat; Moron, Antonio Fernandes; Malinger, Gustavo (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
Objective To construct prenatal age-specific reference intervals for sonographic measurements of the optic nerve sheath diameter (ONSD) during gestation in normal fetuses.Materials and Methods Prospective cross-sectional study of fetuses assessed in antenatal ultrasound units between 2010 and 2014. The examination was based on a technique for the sonographic assessment of ONSD previously published by our group. The mean values and SDs of the ONSD were modeled as a function of the gestational week by curve estimation analysis based on the highest adjusted R2 coefficient. Repeatability tests were performed to assess intraobserver variability and interobserver agreement.Results During the study period 364 healthy fetuses were enrolled. The mean values for the ONSD varied from 0.6 mm at 15–16 weeks to 2.8 mm at 37–38 weeks. The ONSD grows in a linear fashion throughout gestation, with a quadratic equation providing an optimal fit to the data (adjusted R2 = 0.957).Conclusion Sonographic age-specific references for the fetal ONSD are presented. This data may assist in the decision-making process in fetuses with a suspected increase in intracranial pressure, or anomalies affecting the development of optic stalks, such as optic hypoplasia and septo-optic dysplasia.
Keywords: fetus; brain; optic nerve sheath diameter; ultrasound; septo-optic dysplasia